2021
DOI: 10.1111/jpn.13589
|View full text |Cite|
|
Sign up to set email alerts
|

Nicotinic acid supplementation at a supraphysiological dose increases the bioavailability of NAD+ precursors in mares

Abstract: NAD+ deficiency has recently been linked with increased occurrences of congenital abnormalities and embryonic death in human and animal subjects. Early embryonic death is a major component of pregnancy loss in mares and very little is known regarding the requirement for NAD+ in horses. The aim of this study was to quantify NAD+ and its metabolites in the plasma and urine of mares after orally administering an acute dose of nicotinic acid and determine the absorption, metabolism and excretion of this essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The concentration of NA did not differ among the initial plasma samples and the plasma samples collected at the time of FF aspiration in both the vehicle-fed and NA-supplemented mares. In our previous study, we found that the concentration of NA in plasma peaked between 15 min and 1 h following the supplementation of NA [ 25 ]. Therefore, it is not surprising that the concentration of NA did not differ between the initial plasma and the plasma collected at the time of FF aspiration approximately 12–16 h after the final feed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The concentration of NA did not differ among the initial plasma samples and the plasma samples collected at the time of FF aspiration in both the vehicle-fed and NA-supplemented mares. In our previous study, we found that the concentration of NA in plasma peaked between 15 min and 1 h following the supplementation of NA [ 25 ]. Therefore, it is not surprising that the concentration of NA did not differ between the initial plasma and the plasma collected at the time of FF aspiration approximately 12–16 h after the final feed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the absence of NaMN is surprising, considering that we previously detected it in the plasma of mares at low concentrations [ 25 ] that returned to baseline levels at 22 h following the supplementation of NA. In the present study, the NA dose was lower than that used in the previous study, and samples were collected 12–16 h following the final feed as opposed to the time points of 0, 0.25, 0.5, 1, 2, 4, 6 and 22 h [ 25 ] so it is likely that the concentration was below the limits of detection in this study. Additionally, the finding that NaAD was not elevated in the plasma or FF following the dosing period was unexpected, given our previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations